Liquidity Risk Management in Islamic Banking: Comparative Analysis with SUR Methodology for Turkey - Ilter Kucukcolak, Necla; Buyukakin, Figen; Kucukcolak, Recep Ali (Journal of Economic Development, Environment and People, 2019)
Participating banks, emerged as a complementary element in the Turkish financial system since mid-1980s, are continuously increasing their value added to the Turkish banking sector. Therefore, determining whether participation banks and conventional banks differ in liquidity structure and liquidity risk management makes it possible to assess future growth performance of these banks. The aim of this study is to determine factors effecting liquidity risk in Turkish Islamic banking sector. Method used for this purpose is the Seemingly Unrelated Regression (SUR). The result of study indicates that liquidity risk is significantly affected from credit base and funds collected and; increase in them will increase the liquidity risk. Based on our findings, it is possible to estimate factors effecting participation banks liquidity structure and will be a significant input for asset-liability management. This is noteworthy to have robust Islamic banking sector in Turkey and to manage risk they face accurately.